Matrix stiffness in osteoarthritis: from mechanism introduction to biomaterial-based therapies - Huang, Kai; Cai, Haili (Frontiers in Endocrinology, 2025)
Osteoarthritis (OA), the most prevalent joint disorder associated with aging, is characterized by impaired extracellular matrix (ECM) synthesis and the degradation of articular cartilage. It is influenced by various factors, including aging and mechanical stress (such as traumatic injury). Increasing evidence suggests that alterations in cartilage stiffness occur during OA progression, particularly at its onset. This review comprehensively examines how aging and mechanical stress contribute to ECM stiffening, a precursor to irreversible cartilage degradation. We also discuss how increased matrix stiffness disrupts the homeostatic balance between chondrocyte catabolism and anabolism and the mechanotransduction pathways involved in cartilage stiffening. Furthermore, the potential of cartilage engineering to target the stiffness of synthetic materials is explored as a promising approach to advancing cartilage repair and regeneration in OA. A deeper understanding of this research area may not only lead to more innovative strategies for early OA detection and diagnosis but also offer novel insights into OA treatment and prognosis.